2017
DOI: 10.1371/journal.pone.0188121
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screen reveals a role of SPHK2 in dengue virus–mediated apoptosis in hepatic cell lines

Abstract: Hepatic dysfunction is a feature of dengue virus (DENV) infection. Hepatic biopsy specimens obtained from fatal cases of DENV infection show apoptosis, which relates to the pathogenesis of DENV infection. However, how DENV induced liver injury is not fully understood. In this study, we aim to identify the factors that influence cell death by employing an apoptosis-related siRNA library screening. Our results show the effect of 558 gene silencing on caspase 3-mediated apoptosis in DENV-infected Huh7 cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
(76 reference statements)
3
17
0
Order By: Relevance
“…In this view, a recent study on dengue virus-induced liver injury showed that SK-2 is a critical mediator of dengue virus-induced apoptosis of hepatic cells. Downregulating SK-2 by siRNA in various hepatic cell lines, reduced dengue virus-induced caspase-9 and the intrinsic pathway of apoptosis without affecting the extrinsic pathway [39]. This study revealed the same apoptotic pathway to be affected by SK-2 as found in our study on renal mesangial cells.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 83%
“…In this view, a recent study on dengue virus-induced liver injury showed that SK-2 is a critical mediator of dengue virus-induced apoptosis of hepatic cells. Downregulating SK-2 by siRNA in various hepatic cell lines, reduced dengue virus-induced caspase-9 and the intrinsic pathway of apoptosis without affecting the extrinsic pathway [39]. This study revealed the same apoptotic pathway to be affected by SK-2 as found in our study on renal mesangial cells.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 83%
“…RNAi has enabled systematic exploration of host genes involved in virus replication and virulence, thereby allowing identification of novel drug targets (Radoshitzky et al, 2016). Since the last decade, a large number of genome-scale RNAi screens have been conducted, which identified cellular factors required for WNV (Krishnan et al, 2008), DENV (Morchang et al, 2017;Sessions et al, 2009), HIV-1 (Zhou et al, 2008), HCV Lupberger et al, 2015;Tai et al, 2009), IAV (Han et al, 2018;Karlas et al, 2010), JUNV (Lavanya et al, 2013), coronavirus (Staff, 2015), poxvirus (Kilcher et al, 2014), herpesvirus (Griffiths et al, 2013) and polyomavirus (Zhao and Imperiale, 2017) replication. siRNA screens reveal both proviral and antiviral cellular factors and therefore help in understanding the precise nature of virus-host interactions .…”
Section: Genome-wide Sirna Screens To Identify Cellular Factors Requimentioning
confidence: 99%
“…On the one hand, tumour necrosis factor alpha (TNF-α) stimulation of DENV-infected cells during productive infection leads to enhanced death by caspase-3-mediated apoptosis, which is accompanied by a reduced SphK1 activity [ 98 , 99 ]. On the other hand, the activation of SphK2 contributes to DENV-provoked apoptosis in hepatocytes [ 100 ]. Pharmacological inhibition of SphK2 or downregulation via siRNA reduced caspase-3 as well as caspase-9 activity in DENV-infected cells, indicating a pro-apoptotic role of SphK2 via the intrinsic pathway.…”
Section: S1p and Viral Infectionsmentioning
confidence: 99%